Pengaruh Penyuluhan Kesehatan Reproduksi Terhadap Pengetahuan Tentang Dampak Pernikahan Dini Pada Kesehatan Reproduksi - Putri Candhi Ironi; RR. Issac Tri Octaviati; Kurniasari Pratiwi (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2014)
Background: Based on UNICEF data in indonesia the prevalence of child marriage for age 15 years old is about 11%, marriage of age 18 years old is about 35% (UNICEF, 2012). Susenas data from the Central Statistics DIY in 2009 shows that child marriage under 16 years old in DIY is about 8,74 % with the highest percentages in Gunungkidul district (15,40%), Sleman district (7,49%). The percentage was increased in 2010 to 10,81% with the highest percentages is in district of Gunungkidul (16,24%), and district of Kulonprogo (10,81%) and district of Sleman (9,12%).Purpose: To explore the influence of counseling about the impact of early marriage to the reproductive health on the intervention and control group study in SMP PGRI Saptosari, Gunungkidul.Method: Using quasi experimental design with pretest-postest control group design. Sample of the study was total population with 60 respondent. Subjek of study consist of 30 respondens’ control and 30 respondents’ experiment. Control group is the subject who were not given intervention, while experiments group were are the group that given the counseling intervention. Data processing was using t-test.Result: Paired t-test in the control group shows p-value 0,006 with mean 2,19, it can be defined there is a significant difference. Analysis of paired t-test shows p-value in the experiment is 0,000 with mean 2,93, it mean significant difference. The analysis of t-test independent on the pretest’s control group and experiment group shows p-value = 0,05 with mean -1,900 it means there is no significant difference. Analysis t-test independent on posttest’s control group and experiment group shows p-value 0,000 with mean 2,646 which means there is a significant difference.Conclusions: There are no significant difference knowledge in the pretest between the control group and experiment group. There are significant differences of knowledge in the posttest of control group and experiment group with the signification 0,000 (p-value < 0,05).Keywords: reproductive health counseling, early marriage, quasi experimental design, pretest-postest control group design.